GAM Changer: Editing Generalized Additive Models with Interactive Visualization - Wang, Zijie J.; Kale, Alex; Nori, Harsha; Stella, Peter; Nunnally, Mark; Chau, Duen Horng; Vorvoreanu, Mihaela; Vaughan, Jennifer Wortman; Caruana, Rich (2021 Neural Information Processing Systems, 2021)
Recent strides in interpretable machine learning (ML) research reveal that models exploit undesirable patterns in the data to make predictions, which potentially causes harms in deployment. However, it is unclear how we can fix these models. We present our ongoing work, GAM Changer, an open-source interactive system to help data scientists and domain experts easily and responsibly edit their Generalized Additive Models (GAMs). With novel visualization techniques, our tool puts interpretability into action – empowering human users to analyze, validate, and align model behaviors with their knowledge and values. Built using modern web technologies, our tool runs locally in users' computational notebooks or web browsers without requiring extra compute resources, lowering the barrier to creating more responsible ML models. GAM Changer is available at this https URL.